2021
DOI: 10.3390/brainsci11111485
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Intrinsic Functional Connectivity Changes of Locus Coeruleus from Childhood to Older Adults

Abstract: The locus coeruleus is critical for selective information processing by modulating the brain’s connectivity configuration. Increasingly, studies have suggested that LC controls sensory inputs at the sensory gating stage. Furthermore, accumulating evidence has shown that young children and older adults are more prone to distraction and filter out irrelevant information less efficiently, possibly due to the unoptimized LC connectivity. However, the LC connectivity pattern across the life span is not fully examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Therefore, it is difficult to determine whether insomnia or anxiety and depression had a greater impact on the FC of LC-IFG and LC-SMG in that study. The FC of LC is also influenced by age, differences in demographic characteristics can also contribute to inconsistent results ( Zhang et al, 2016 ; Song et al, 2021 ). In addition, the difference in the method of LC localization may also play roles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to determine whether insomnia or anxiety and depression had a greater impact on the FC of LC-IFG and LC-SMG in that study. The FC of LC is also influenced by age, differences in demographic characteristics can also contribute to inconsistent results ( Zhang et al, 2016 ; Song et al, 2021 ). In addition, the difference in the method of LC localization may also play roles.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies report non-overlapping spontaneous activation dynamics from different sites in the LC that associate with and drive different cortical states, suggesting the presence of distinct neural ensembles in the LC that regulate multiple cortical states, instead of a homogeneous arousal-related release of noradrenaline across the cortex (41). Although fMRI provides a comprehensive view of LC function due to this nucleus’ extensive and diffuse cortical projections, this technique is limited by low spatial resolution, which could explain why previous resting-state fMRI studies focused on the LC obtained inconsistent results (16,17). The high connectivity heterogeneity of the LC shown in our study indicates that using the LC as a single, homogeneous ROI might not be the best approach to assess connectivity in this region.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because this region modulates various behavioral functions and widespread brain regions in a very precise manner (15). Furthermore, studies using fMRI to describe connectivity in the LC report heterogeneous results -possibly because the localization methods, the studied populations and preprocessing pipelines often differ (16)(17)(18)(19) -and a similarity gradient-based approach might be better suited to characterize its functional organization by mitigating the effect of heterogeneous individual differences in connectivity and imaging acquisition-related noise, since it is less affected by e.g. ROI inaccuracies (20).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the relationship between age and LC connectivity may be more complex than just linear decrease (Jacobs et al, 2018; I. Song et al, 2021). Different results might have been obtained if the older group was divided into middle-aged adults (55-65) and older (65-80) adults.…”
Section: Discussionmentioning
confidence: 99%
“…A curvilinear association between the age and functional connectivity of the left LC to the bilateral cortical areas such as temporal pole, posterior middle temporal gyrus angular gyrus, and inferior frontal gyrus, as well as right posterior cingulate cortex was observed by Jacobs and colleagues (Jacobs et al, 2018). Recently, Song, Neal and Lee found a positive quadratic relationship between the age and LC connectivity with sensory regions and a negative quadratic association between the age and LC connectivity with frontal regions (Song et al, 2021).…”
Section: Introductionmentioning
confidence: 99%